Fasting Plasma Glucose Level Independently Predicts the Mortality of Patients with Coronavirus Disease 2019 Infection: A Multicenter, Retrospective Cohort Study - Chang, Min Cheol; Hwang, Jong-Moon; Jeon, Jae-Han; Kwak, Sang Gyu; Park, Donghwi; Moon, Jun Sung (Endocrinology and metabolism (Seoul), 2020)
Coronavirus disease 2019 (COVID-19) has become a global pandemic, which prompts a consensus for the necessity to seek risk factors for this critical disease. Risk factors affecting mortality of the disease remain elusive. Diabetes and hyperglycemia are known to negatively affect a host's antiviral immunity. We evaluated the relationship between a history of diabetes, fasting plasma glucose (FPG) levels and mortality among severely ill patients with COVID-19. This was a retrospective cohort study that assessed 106 adult inpatients (aged ≥18 years) from two tertiary hospitals in Daegu, South Korea. The participants were transferred to tertiary hospitals because their medical condition required immediate intensive care. The demographic and laboratory data were compared between COVID-19 patients who survived and those who did not. Compared with the survivor group, age, and the proportions of diabetes, chronic lung disease and FPG were significantly higher in the deceased group. In the Cox proportional hazards regression model for survival analysis, FPG level and age were identified as significant predictors of mortality (P<0.05). The threshold values for predicting high mortality were age >68 years and FPG of 168 mg/dL, respectively. Among those without diabetes, high FPG remained a significant predictor of mortality (P<0.04). High FPG levels significantly predicted mortality in COVID-19, regardless of a known history of diabetes. These results suggest intensive monitoring should be provided to COVID-19 patients who have a high FPG level.